Environmental and historical controls of floristic composition across the South American Dry Diagonal. (15th May 2015) - Neves, Danilo M.; Dexter, Kyle G.; Pennington, R. Toby; Bueno, Marcelo L.; Oliveira Filho, Ary T.
Abstract Aim The aim of this study was to test the role of environmental factors and spatially autocorrelated processes, such as historical fragmentation and dispersal limitation, in driving floristic variation across seasonally dry tropical forests (SDTFs) in eastern South America. Location SDTFs extending from the Caatinga phytogeographical domain of north‐eastern Brazil to the Chaco phytogeographical domain of northern Argentina, an area referred to as the Dry Diagonal. Methods We compiled a database of 282 inventories of woody vegetation in SDTFs from across the Dry Diagonal and combined this with data for 14 environmental variables. We assessed the relative contribution of spatially autocorrelated processes and environmental factors to the floristic turnover among SDTFs across the Dry Diagonal using variation partitioning methods. In addition, we used multivariate analyses to determine which environmental factors were most important in explaining the turnover. Results We found that the environmental factors measured (temperature, precipitation and edaphic conditions) explained 21.3% of the variation in species composition, with 14.1% of this occurring independently of spatial autocorrelation. A spatially structured fraction of 4.2% could not be accounted for by the environmental factors measured. The main axis of compositional variation was significantly correlated with a north–south gradient in temperature regime. At the extreme south of the Dry Diagonal, a cold temperature regime, in which frost occurred, appeared to underlie floristic similarities between chaco woodlands and southern SDTFs. Main conclusions Environmental variables, particularly those related to temperature regime, seem to be the most significant factors affecting variation in species composition of SDTFs. Thus historical fragmentation and isolation alone cannot explain the turnover in species composition within SDTFs, as is often assumed. Compositional and environmental heterogeneity needs to be taken into account both to understand the past distribution of SDTFs and to manage and conserve this key tropical biome.